Determinación de valores Séricos y Factores asociados en Caninos Domésticos (canis familiaris) del Barrio Centro de la Parroquia Pastocalle. - Benavides Cueva, Oscar Raúl (2018)
This research was carried out in the Cotopaxi Province, Latacunga Canton, San Juan de Pastocalle Parish, Centro Neighborhood with the purpose of determining serum values and associated factors within dogs (canis familiaris). Seventy-five canines were the sample; blood samples were taken for laboratory analysis, a questionnaire of 20 questions was applied to the owner of each dog to know the associated factors. In SAN FRANCISCO laboratory located in Ambato city, a complete blood count was performed; in addition to Glucose, Urea, BUN, Creatinine, AST, and ALT. Then each test was analyzed, classifying them from 1 to 5 years and more than 5 years to facilitate the study, these data were tabulated, and related to the answers from questionnaires to identify the condition of the dogs according to the age range , with the following results: Red series: anemia 3.45% in 1 to 5 years and 1.72% in 5 years onwards, absolute polycythemia 12.1% in 1 to 5 years, and 11.8% in 5 years on, relative polycythemia 13.79% in 1 to 5 years and 5.9 % in 5 years onwards determining that there is an adequate management in regard to the feeding of the canines; White series: eosinophils are the highest with 8% in 1 to 5 years and 10.67% in 5 years and older, associating with surveys with moderate stress levels; Platelets: decreased by 10.67% in 1 to 5 years and 5.33% in 5 years onwards, comparing, determining that there is thrombocytopenia adducing is the lack of periodic veterinary control, vaccines and treatments, linked to the management of the owners; Blood chemistry: decreased glucose hypoglycemia 13.33% in 1 to 5 years and 4% in 5 years onwards, Urea elevated 10.85% in 1 to 5 years and 11.27% in 5 years and up, associating these values with an inadequate diet dehydration.